HUBUNGAN ANTARA SLEEP HYGIENE DENGAN TINGKAT INSOMNIA PADA LANSIA DI KECAMATAN JEBRES KELURAHAN GANDEKAN RW 05 SURAKARTA - Putri Wulan Dhari; Ika Silvitasari (Nusantara Hasana Journal, 2022)
Insomnia is the most common sleep disorder experienced by the elderly. Sleep disturbances in the elderly can have a negative impact, especially on the health conditions of the elderly. Sleep hygiene is a way of training to form habits so that sleep becomes quality based on activities carried out before bed. The purpose of the study was to determine "The Relationship Between Sleep Hygiene and Insomnia Levels in the Elderly in Jebres District, Gandekan Village, RW 05 Surakarta". This research is a quantitative observational analytic. The sample in this study was 40 samples which were calculated using the Slovin formula. The research instrument used the IRS (Insomnia Rating Scale) to measure the degree of insomnia and the SHI (Sleep Hygiene Index) measuring instrument to measure the sleep hygiene habits of the elderly. The analysis used is univariate and bivariate using Spearman Rank test. The results of data analysis with the Rank - Spearman test obtained a value of Sig = 0.000 < (0.05) which means Ho is rejected and Ha is accepted which means "There is a relationship between Sleep Hygiene and Insomnia in the Elderly in Jebres Gandekan District, RW 05 Surakarta.